Anticipatory pleasure predicts effective connectivity in the mesolimbic system - Li, Zhi; Yan, Chao; Xie, Wei-Zhen; Li, Ke; Zeng, Ya-Wei; Jin, Zhen; Cheung, Eric F. C.; Chan, Raymond C. K. (Frontiers in Behavioral Neuroscience, 2015)
Convergent evidence suggests the important role of the mesolimbic pathway in anticipating monetary rewards. However, the underlying mechanism of how the sub-regions interact with each other is still not clearly understood. Using dynamic causal modeling, we constructed a reward-related network for anticipating monetary reward using the Monetary Incentive Delay Task. Twenty-six healthy adolescents (Female/Male = 11/15; age = 18.69±1.35 years; education = 12±1.58 years) participated in the present study. The best-fit network involved the right substantia nigra/ventral tegmental area, the right nucleus accumbens and the right thalamus, which were all activated during anticipation of monetary gain and loss. The substantia nigra/ventral tegmental area directly activates the nucleus accumbens and the thalamus. More importantly, monetary gain modulated the connectivity from the substantia nigra/ventral tegmental area to the nucleus accumbens and this was significantly correlated with subjective anticipatory pleasure (r = 0.649, p < 0.001). Our findings suggest that activity in the mesolimbic pathway during the anticipation of monetary reward could to some extent be predicted by subjective anticipatory pleasure.